Magnetic resonance imaging of the caudal portion of the digastric muscle in canine idiopathic facial neuropathy. Issue 4 (4th May 2021) - McGregor, Ombeline; Plested, Mark J.; Beltran, Elsa
Abstract: Idiopathic is the most common etiology for acute onset of facial neuropathy in dogs with limited number of studies describing MRI characteristics. A retrospective, observational study was performed using archived records, aiming to describe the MRI features of the caudal portion of the digastric muscle in dogs diagnosed with idiopathic facial neuropathy and to determine correlation with prognosis. Client‐owned dogs presented to a referral hospital between 2009 and 2019, diagnosed with unilateral idiopathic facial neuropathy and having undergone MRI, with images including the caudal portion of the digastric muscle, were included ( n  = 19). MRI appearance of the affected muscle, including degree of muscle atrophy, signal intensity, enhancement post‐contrast, and enhancement characteristics of the affected facial nerve, was described and compared to the contralateral, clinically unaffected caudal portion of the digastric muscle. Correlation between MRI appearance and outcome at 1‐month and 3‐months following onset of clinical signs was investigated. The majority of patients demonstrated some degree of muscle atrophy ( n  = 17, 89%), hyperintensity in T2W ( n  = 17, 89%), and pre‐contrast T1W ( n  = 15, 79%) images, as well as contrast enhancement of the affected muscle ( n  = 14, 74%) and affected facial nerve ( n  = 9, 47%). There was no statistically significant correlation between atrophy or enhancement of the affected caudal portion of the digastric muscle nor between enhancement of the affected facial nerve and outcome. Hyperintensity both in T2W images and pre‐contrast T1W images was significantly correlated with a worse prognosis. Ensuring inclusion and evaluation of this muscle in MRI may therefore be indicated in canine idiopathic facial neuropathy.